Functional RNA delivery targeted to dendritic cells by synthetic nanoparticles. (September 2012) - McCullough, Kenneth C; Bassi, Isabelle; Démoulins, Thomas; Thomann-Harwood, Lisa J; Ruggli, Nicolas
Dendritic cells (DCs) are essential to many aspects of immune defense development and regulation. They provide important targets for prophylactic and therapeutic delivery. While protein delivery has had considerable success, RNA delivery is still expanding. Delivering RNA molecules for RNAi has shown particular success and there are reports on successful delivery of mRNA. Central, therein, is the application of cationic entities. Following endocytosis of the delivery vehicle for the RNA, cationic entities should promote vesicular membrane perturbation, facilitating cytosolic release. The present review explains the diversity of DC function in immune response development and control. Promotion of delivered RNA cytosolic release is discussed, relating to immunoprophylactic and therapeutic potential, and DC endocytic machinery is reviewed, showing how DC endocytic pathways influence the handling of internalized material. The potential advantages for application of replicating RNA are presented and discussed, in consideration of their value and development in the near future.